RETRACTED: Education of the elderly people in the system of higher education institutions - Vysotskaya Inna; Yovanovich Tamara; Sinenko Tatyana; Bogomazova Victoria; Toporkova Olga (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001